THE PROGNOSTIC SIGNIFICANCE OF MYXOID MATRIX IN RETROPERITONEAL WELL-DIFFERENTIATED LIPOSARCOMA - A. Yu. Volkov; N. A. Kozlov; S. N. Nered; I. S. Stilidi; A. M. Stroganova; P. P. Arkhiri; E. Yu. Antonova; S. A. Privezentsev (Сибирский онкологический журнал, 2021)
Objective: to assess the influence of the myxoid matrix in retroperitoneal well-differentiated liposarcoma(WDLPS ) on the long-term results of surgical treatment of patients.Material and Methods. The study included 111 patients with primary retroperitoneal WDLPS who underwent radical surgical treatment in Federal State Budgetary Institution «N.N. Blokhin National Medical Research Center of Oncology» of the Ministry of Health of the Russian Federation. Histological slides of all surgical specimens were reviewed by experienced pathologist and reclassified according to criteria of WHO (2013) for histological subtypes of the WDLPS . Patients were divided into groups depending on presence or absence of the myxoid matrix in WDLPS and enrolled in intergroup analysis of overall (OS ) and recurrence-free (RFS) survival.Results. OS was significantly worse in the group of patients with the myxoid matrix in the tumor (p=0.002; log-rank test). The median OS was 142 (95 % CI , 108, 176) months in the group without the myxoid matrix, and 84 (95 % CI , 29, 139) months in the group with the myxoid matrix. The 5-year survival rates were 79 % and 44 % in the groups without myxoid matrix and with myxoid matrix, respectively. RFS was also significantly worse in the group of patients with the myxoid matrix than in the group of patients without the myxoid matrix (p=0.006; log-rank test). The median RFS was 55 (95 % CI , 38, 72) months in the WDLPS group without the myxoid matrix, and 31 (95 % CI , 15, 47) months in the WDLPS group with the myxoid matrix. The 2-year RFS rates were 75 % and 44 % in the groups without the myxoid matrix and with the myxoid matrix, respectively.Conclusion. The results of the study demonstrated that the presence of the myxoid matrix in WDLPS was associated with poor prognosis. We believe that the presence of the myxoid matrix in WDLPS can serve as an effective morphological marker of a less favorable prognosis for retroperitoneal WLPS .